AI-ASSISTED ENGLISH VOCABULARY LEARNING: A NEW APPROACH FOR DIGITAL-AGE STUDENTS - Zhiger Zholdy; Nabidullin S. Aibolat (Research Retrieval and Academic Letters, 2025)
This article investigates the transformative role of Artificial Intelligence (AI) in facilitating English vocabulary acquisition for modern students. The digital age demands innovative educational approaches, and AI offers solutions to the limitations of traditional methods. The study aims to analyze the key AI-driven methodologies, such as adaptive learning and spaced repetition, and evaluate their effectiveness in enhancing vocabulary retention, engagement, and autonomy. The research employs a mixed-methods approach, including a comprehensive review of recent scholarly literature and a comparative analysis of popular AI-powered platforms like Duolingo, Memrise, and conversational AI chatbots. The findings indicate that AI-assisted learning leads to statistically significant improvements in long-term vocabulary retention and fosters higher levels of student motivation through personalized and interactive experiences. The article concludes that the integration of AI into language learning curricula is not merely beneficial but essential for meeting the needs of digital-native learners, highlighting both its practical implications and potential challenges.